2017
DOI: 10.3892/mmr.2017.6622
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B attenuates the inflammatory response, oxidative stress and apoptosis induced by traumatic spinal cord injury via inhibition of p53 signaling in adult rats

Abstract: Schisandrin B is an active monomer of the Chinese magnolia vine (Schisandra chinensis) that can reduce transaminase activity in liver cells, inhibit lipid peroxidation, enhance antioxidant status, has protective effects in the liver and has antitumor effects. The present study investigated the potential protective effects of schisandrin B on the p53 signaling pathway in attenuating the inflammatory response, oxidative stress and apoptosis induced by traumatic spinal cord injury (TSCI) in adult rats. Behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…All rats were anesthetized with intraperitoneal 300 mg/kg chloral hydrate (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) and the T8-T10 spinal column was exposed. The Impact One™ Stereotaxic Impactor (Leica Microsystems GmbH, Wetzlar, Germany) was inserted through the atlanto-occipital membrane at T9 and was an SCI model was established as previously described (8). Rats of the sham group were anesthetized with intraperitoneal 300 mg/kg chloral hydrate (Sigma-Aldrich; Merck KGaA) without the induction of SCI.…”
Section: Animals and Treatments A Total Of 16 Adult Femalementioning
confidence: 99%
“…All rats were anesthetized with intraperitoneal 300 mg/kg chloral hydrate (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) and the T8-T10 spinal column was exposed. The Impact One™ Stereotaxic Impactor (Leica Microsystems GmbH, Wetzlar, Germany) was inserted through the atlanto-occipital membrane at T9 and was an SCI model was established as previously described (8). Rats of the sham group were anesthetized with intraperitoneal 300 mg/kg chloral hydrate (Sigma-Aldrich; Merck KGaA) without the induction of SCI.…”
Section: Animals and Treatments A Total Of 16 Adult Femalementioning
confidence: 99%
“…Schisandrin B (Sch B) is a bioactive ingredient isolated from the plant, Schisandra chinensis (also known as the five-flavor berry or Wu Wei Zi). Several lines of evidence have shown that Sch B has anti-oxidative, anti-inflammatory, and anti-tumor activities [ 10 , 11 , 12 ]. Recent studies have shown that Sch B can be used as a treatment for bacterial or lipopolysaccharide-induced neuroinflammation [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in vitamin C concentration in the liver of test animals upon treatment with γ‐schisandrin also validates its hepatoprotective ability. Another individual lignin, Schisandrin B was also found to counter oxidative harm to liver tissues (Thandavarayan et al, ; Xin et al, ). In one scientific study, the hepatoprotective mechanism against acetaminophen‐induced liver injury of six Schisandra lignans (deoxyschisandrin, Schisantherin A, Schisandrin B, Gomisin A, Schisandrin C, and schisandrin) was elucidated.…”
Section: Resultsmentioning
confidence: 99%